Effect of Juglone on Seed Germination and Seedling Growth of Endemic Species Aubrieta olympica and Arabis drabiformis in Tissue Culture Conditions - Akin, Betul; Kocacaliskan, Ismail (FERDINAND BERGER SOEHNE, 2016)
The aim of this study was to research if juglone increases seed germination, seedling growth and chlorophyll content of the endemic plant species Aubrieta olympica BOISS. and Arabis drabiformis BOISS. in tissue culture conditions. Juglone was found to increase seed germination at both 10(-5) and 10(-6) M concentrations. However, elongation, fresh-dry weights and chlorophyll contents of the seedlings were increased considerably only at 10(-5) M juglone concentration. The increase was significantly different according to control and to the other juglone concentrations. On the other hand, 10(-3) and 10(-4) M juglone concentratios caused significant decreases in the plant growth parameters and caused thin and yellowish seedlings. It has been concluded that 10(-5) M juglone may be used as a component of MS medium in tissue culture for efficient propagation of the plant species studied which are under extinction risk.
Keywords: Arabis drabiformis BOISS.; Aubrieta olympica BOISS. - Endemic plant species; juglone; growth; chlorophyll content; tissue culture; WALNUT LEAF; ULUDAG; BURSA; MICROPROPAGATION; MUSKMELON; EXTRACTS; PLANTS; RARE; Plant Sciences